2020
DOI: 10.1038/s41467-020-18100-9
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of Al2O3/2D perovskite heterostructure dielectric for high performance MoS2 phototransistors

Abstract: Two-dimensional (2D) Ruddlesden-Popper perovskites are currently drawing significant attention as highly-stable photoactive materials for optoelectronic applications. However, the insulating nature of organic ammonium layers in 2D perovskites results in poor charge transport and limited performance. Here, we demonstrate that Al 2 O 3 /2D perovskite heterostructure can be utilized as photoactive dielectric for high-performance MoS 2 phototransistors. The type-II band alignment in 2D perovskites facilitates effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…Compared to phototransistors with a linear photoresponse reported elsewhere, our dual‐gate phototransistors exhibited many superiorities attributed to the layered 2D material and device configuration. Our devices exhibited detectivity three orders of magnitude higher than a HfO 2 ‐encapsulated MoS 2 phototransistor (≈2 × 10 10 Jones), [ 20 ] the speed three orders faster than a dual‐gate MoS 2 phototransistor (with photoresponse time > 50 s), [ 22 ] and to be more stable than perovskite‐based [ 21 ] and organic‐based [ 23 ] phototransistors. For the dual‐gate MoS 2 phototransistor with similar architecture, [ 22 ] only n‐channel can be turned on and the photoresponse was boosted by enhancing the photogating effect through the interface coupling, which would be weakened for thick MoS 2 film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to phototransistors with a linear photoresponse reported elsewhere, our dual‐gate phototransistors exhibited many superiorities attributed to the layered 2D material and device configuration. Our devices exhibited detectivity three orders of magnitude higher than a HfO 2 ‐encapsulated MoS 2 phototransistor (≈2 × 10 10 Jones), [ 20 ] the speed three orders faster than a dual‐gate MoS 2 phototransistor (with photoresponse time > 50 s), [ 22 ] and to be more stable than perovskite‐based [ 21 ] and organic‐based [ 23 ] phototransistors. For the dual‐gate MoS 2 phototransistor with similar architecture, [ 22 ] only n‐channel can be turned on and the photoresponse was boosted by enhancing the photogating effect through the interface coupling, which would be weakened for thick MoS 2 film.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, high‐resolution and quantitative light detection requires a linear photoresponse with high responsivity, which can be realized by phototransistors if the photoconductive gain is constant with respect to light intensity. Several approaches have been reported recently about the gain tunability of phototransistors, such as adjusting the Fermi level by gate control, [ 20 ] using photoactive perovskite dielectrics based on photoinduced ionic migration, [ 21 ] and rearranging the carriers with a vertical electric field produced by dual‐gating. [ 22,23 ] Despite exhibiting a linear photoresponse with high responsivity, the first two of these approaches are limited by unexceptional detectivity (due to large 1/ f noise) and unsatisfactory device stability, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, various arrangements of graded RPP phases (with the changing n values) capable to establish tunable band alignment and associated energy cascade transfer processes have also been proposed and widely studied for different utilization scenarios. [32][33][34][35][36][37][38] Herein, utilizing this unique nature of RPPs, high-quality RPP films composed of the relatively short-chain iBA as spacer cations (iBA 2 (MA) n-1 Pb n I 3n+1 ) with gradient band alignments are successfully synthesized by a simple one-step spin-coating process. It is observed that the graded RPP phases distribute sequentially with the increasing n values towards the film surface.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant works, based on different mechanism, that focus on the realization of photodetectors with high sensitivity, have been carried out, which has great significance for weak light sources and long detection distance light sources detection. [ 170,171 ] Normally, the sensitivity of a photodetector is described by specific detectivity D *, which is determined by responsivity and noise level. To obtain high specific detectivity, it is necessary to improve photoresponsivity and reduce noise level.…”
Section: Optoelectronic Devicesmentioning
confidence: 99%